Normotensive, Oversized Pheochromocytoma in Twin-Pregnancy: Analysis of Therapeutic Challenges in a Rare Case. (22nd May 2019) - Özveren, Bora; Ulugöl, Halim; Türkeri, Levent
Abstract : An asymptomatic, normotensive 36-year-old woman in the second trimester of a twin-gestation was diagnosed with a 11 cm adrenal pheochromocytoma. Considering the hemodynamic stability of the patient, tumor size, and gestational age, the therapeutic decision of a multidisciplinary team ensued open surgical excision without any preoperative antihypertensive preparation. Following successful removal of pheochromocytoma, the patient had a normal subsequent course of pregnancy and cesarean section delivery of healthy twins at term. This unique case of a normotensive, incidental, large-sized pheochromocytoma in a twin-pregnancy illustrates that the decisions of management in such a rare occurrence should be based on individual features of the patient. Our experience supports that α -adrenergic blockade may not be essential in normotensive pheochromocytoma in pregnancy and open-surgery remains as a safe approach in the management of large adrenal tumors in twin-pregnant patients following a multidisciplinary consultation.